Economics of Civil Conflict: Evidence from the Punjab Insurgency - Prakarsh Singh (Institute for the Study of Labor (IZA), 2016)
The Punjab Insurgency in India (1978-1993) took the lives of over 20,000 people. Yet, there has been little research on the economic causes and consequences of the conflict in Punjab, which has been classified as a civil war and also an insurgency. In this article, I delve into some of the reasons for why Punjab suffered such a prolonged and bloody insurgency. Finally, I consider the macro and microeconomic effects of the conflict in Punjab that affected every walk of life and perhaps continue to do so today.
Keywords: D74; 330; Punjab; conflict; civil war; insurgency; India